Percutaneous coronary intervention strategies in patients with ST-segment elevation myocardial infarction and multivessel coronary artery disease. (November 2017) - Thomas, Michael P.; Bates, Eric R.
Abstract : Purpose of review: This review aims to summarize recent reports on percutaneous coronary intervention (PCI) strategies for patients with ST-elevation myocardial infarction (STEMI) and multivessel coronary artery disease (CAD). Recent findings: Recent randomized clinical trials and meta-analyses have suggested that patients with STEMI and multivessel CAD may benefit more from multivessel PCI (either multivessel primary PCI or staged PCI before hospital discharge) than culprit vessel-only primary PCI. These reports have changed clinical practice guideline recommendations that now conclude that multivessel PCI may be considered in selected hemodynamically stable patients with significant noninfarct artery stenoses based on anatomic criteria alone. Fractional flow reserve measurement can document functional significance in nonculprit stenoses, but fractional flow reserve-guided PCI has not been shown to impact mortality or myocardial infarction rates. Additionally, nonculprit artery chronic total occlusion PCI was not effective in improving left ventricular function in one randomized trial. Summary: Multivessel primary PCI or staged PCI is effective and safe in selected patients with STEMI and multivessel coronary disease. Future randomized controlled trials are needed to define the optimal timing of multivessel PCI, as well as the appropriate use of PCI in nonculprit stenoses.